Seroprevalence of Mycoplasma Infection in Broiler Population of Assam - Sarmah, Rishabh; Dutta, Biswajit; Konch, Chambal; Saikia, G. K.; Gogoi, S. M.; Tamuly; Deka, Abhijit; Hazarika, Navalakhi (International Journal of Bio-resource and Stress Management, 2022)
The experiment was conducted in the Department of Veterinary Pathology, C.V.Sc, A.A.U., Khanapara, Guuwahati, Assam, India during September, 2020−August, 2021. Avian Mycoplasmosis is a severe threat to the poultry industry. Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) represent the most important Avian Mycoplasma spp. worldwide in the poultry industry. All age groups of chickens and turkeys are susceptible to infection. Most of the outbreaks were recorded between 3rd and 6th weeks of age. The disease is characterized by respiratory rales, coughing, nasal discharge, conjunctivitis, sinusitis and air sac lesions. In the present study, a total of 400 sera were tested for detection of antibodies from 29 farms from 11 different locations of Kamrup (M) and Kamrup (R) district, Assam. For detection of Mycoplasma antibodies, indirect ELISA was performed by using commercially available kits for MG and MS (IDEXX Laboratories). Out of the total samples tested, 13.25% showed sero-positivity for MG and 7.25% showed sero-positivity for MS. Among different age groups, highest sero-positivity was recorded in age group of above 5 weeks (8.5%) and lowest sero-positivity was recorded in birds of age 3−4 weeks (0.75%) for MG. For MS, the highest sero-positivity was recorded in birds of age group of above 5 weeks (5.25%) and lowest sero-positivity was recorded from age 3−4 weeks (0.5%). Season-wise highest sero-positivity was recorded in winter (6.5%), followed by post-monsoon (4.25%), monsoon (1.75%) and pre-monsoon (0.75%) for MG. In case of MS, highest sero-positivity was recorded in post-monsoon (3%), followed by winter (2.75%), monsoon (1%) and pre-monsoon (0.5%).